Pengalaman Perawat Melakukan Triase Lima Level pada Pasien dengan Nyeri Dada - Zulmah Astuti; Indah Winarni; Ali Haedar (Jurnal Gema Keperawatan, 2014)
This aims of this Study is to explore the experience of nurses doing the five-level of triage process to patients with chest pain in the emergency department. This Study used a qualitative design with an  interpretive phenomenological approach . Data were collected through interviewed to the six nurses who worked recently in triage room in emergency department of Sanglah Hospital. Data were transcripts and analyzed using Miles Huberman method. The results showed seven themes, their were the initial assessment of patients, the Act of first aid in patient, the assessment of hemodynamic, the further of examination, the assessment of chest pain, the consideration used in determining the level of urgency of the patient and the duration of triage process for each patient.